Practical Perfect Absorption in Monolayer Graphene by Prism Coupling - Sangjun Lee; Sangin Kim (IEEE Photonics Journal)
We propose a practical perfect absorber comprising three dielectric layers for prism coupling with monolayer graphene embedded in the middle layer. Since the loss rate can be controlled by the graphene position within the middle layer, the limitation on the material index choice is greatly relieved, overcoming the problem of the previously studied similar structure. It is shown that F2 glass-silica-quartz structure enables perfect absorption if the silica layer thickness and the graphene position are properly chosen. The proposed structure can adopt a thin layer of any absorbing material for perfect absorption owing to the adaptive loss rate feature.